Behavioral strategies and physical therapy for polycystic ovary syndrome - Siusiuka, V. G.; Serhiienko, M. Yu.; Pavliuchenko, M. I.; Shapoval, О. S.; Haidai, N. V.; Kolokot, N. G.; Сюсюка, Володимир Григорович; Сергієнко, Марина Юріївна; Павлюченко, Михайло Іванович; Шаповал, Ольга Сергіївна; Гайдай, Наталія Вікторівна; Колокот, Наталя Григорівна (My University, 2023)
Polycystic ovarian syndrome (PCOS) is a prevailing endocrine and metabolic disorder occurring in about 20% of females in reproductive age. Most symptoms of PCOS arise early during puberty [1, 2, 3, 4, 5, 6].
Keywords: тези доповідей